The role of the Pretoria-Pietersburg railway line in the Northern Transvaal during the South African War (1899-1902) - Pretorius, F. (Fransjohan) (University of Pretoria, 2021)
Dissertation (MSocSci (History))--University of Pretoria, 2020.